Sarong party girls - Tan, Cheryl Lu-lien (New York, NY William Morrow, an imprint of HarperCollins Publishers, 2016)
On the edge of twenty-seven, Jazzy hatches a plan for her and her best girlfriends: Sher, Imo, and Fann. Before the year is out, these Sarong Party Girls will all have spectacular weddings to expat ang moh-- caucasian-- husbands, with Chanel babies (half-white children--the ultimate status symbol) quickly to follow. Razor-sharp, spunky, and cheerfully brand-obsessed, Jazzy is a woman who plays to win. As she fervently pursues her quest to find the right husband, this driven yet tenderly vulnerable gold digger reveals the contentious gender politics and class tensions thrumming beneath the shiny exterior of Singapore's glamorous nightclubs and busy streets, its grubby wet markets and crowded hawker centers. Moving through her colorful, stratified world, she realizes she cannot ignore the troubling incongruity of new money and old-world attitudes that threatens to crush her dreams. Can Jazzy use her cunning and good looks to rise up the ladder in Asia's international capital? Vividly told in Singlish-- colorful Singaporean English with its distinctive cadence and slang-- Sarong Party Girls brilliantly captures the unique voice of this young, striving woman caught between worlds. With remarkable vibrancy and empathy, Cheryl Lu-Lien Tan brings not only Jazzy, but her city of Singapore, to dazzling, dizzying life.
Keywords: Dating (Social customs) -- Fiction; Fashion -- Fiction; Singaporean fiction (English); Dating (Social customs) -- Singapore